Eric Bogle’s No Man’s Land and the grave of Willie McBride at the Somme - Walsh, Michael J. K. (2021)
Eric Bogle wrote No Man’s Land in 1975. When it was released as The Green Fields of France by Davey Arthur and the Fureys in 1979 the song topped the Irish charts, while as far away as Australia it was declared one ‘of the most striking musical essays yet written on the futility of war.’ Yet No Man’s Land has been associated with controversy too: branded a rebel song in Ulster during The Troubles, singled out by Tony Blair as a ‘peace anthem’ and prelude to the Good Friday Agreement in 1998, and controversially chosen by the Royal British Legion for the Poppy Day appeal in 2014. In addition to exploring the ‘complex relations between cultural and political history’ in Ireland, this article also looks at the making of the documentary film ‘Eric Bogle: Return to No Man’s Land’ (by Dan Frodsham) in which Bogle returned to the grave of Willie McBride on the 100th anniversary of the Battle of the Somme to recite his poem to the now famous Inniskilling. To Bogle’s surprise the grave had become a pilgrimage site for this, an entirely fictional, Irish martyr created then immortalized in his own composition written four decades earlier.